Serum IL-37 Level Is Associated with Rheumatoid Arthritis and Disease Activity: A Meta-Analysis. (8th February 2021) - Cao, Shengnan; Shi, Haojun; Sun, Guodong; Chen, Yuanzhen; Hou, Guangjian; Wang, Dandan; Shi, Bin
Abstract : Interleukin-37 (IL-37) inhibits the pathogenesis of rheumatoid arthritis (RA) via downregulating proinflammatory cytokines. Accordingly, we performed an analysis to accurately assess the relationship between serum IL-37 cytokine levels and disease activity of RA. Subgroup analysis and sensitivity analysis were applied to explore the sources of heterogeneity. Correlation coefficient (r ) was utilized to evaluate the relationship between IL-37 and disease activity of RA patients. Ten studies were included into the research. Functional analysis revealed elevated serum IL-37 concentrations in RA patients (SMD = 1.61, P < 0.00001 ). The relationship between serum IL-37 levels and disease activity was statistically significant (C-reactive protein: r = 1.47, P = 0.0002 ; erythrocyte sedimentation rate: r = 1.55, P < 0.00001 ; rheumatoid factor: r = 1.40, P = 0.004 ; tumor necrosis factor⁃ α : r = 1.64, P = 0.0003 ; Disease Activity Score for 28 joints: r = 1.63, P < 0.00001 ; tender joint count: r = 1.48, P < 0.00001 ; and swollen joint count: r = 1.52, P = 0.0003 ), but anti-CCP was not significant (anti-CCP: r = 0.98, P = 0.72 ). In summary, these data are suggesting that the elevated serum level of IL-37 in RA is positively correlated with the disease activity of RA, suggesting a role for IL-37in the pathogenesis of RA.